Skin autofluorescence corresponds to microvascular reactivity in diabetes mellitus - Škrha, Jan; Horová, Eva; Šoupal, Jan; Valeriánová, Anna; Malík, Jan; Prázný, Martin; Zima, Tomáš; Kalousová, Marta; Škrha, Jan (Journal of diabetes and its complications, 2022)
Advanced glycation accelerated by chronic hyperglycaemia contributes to the development of diabetic vascular complications throughout several mechanisms. One of these mechanisms is supposed to be impaired microvascular reactivity, that precedes significant vascular changes. The aim of this study was to find an association between advanced glycation, the soluble receptor for AGEs (sRAGE), and microvascular reactivity (MVR) in diabetes. Skin autofluorescence (SAF), which reflects advanced glycation, was assessed by AGE-Reader, MVR was measured by laser Doppler fluxmetry and evaluated together with sRAGE in 43 patients with diabetes (25 Type 1 and 18 Type 2) and 26 healthy controls of comparable age. SAF was significantly higher in patients with diabetes compared to controls (2.4 ± 0.5 vs. 2.0 ± 0.5 AU; p < 0.01). Patients with diabetes with SAF > 2.3 AU presented significantly worse MVR in both post-occlusive reactive hyperaemia (PORH) on the finger and forearm, and thermal hyperaemia (TH), compared to patients with SAF < 2.3 AU. SAF was age dependent in both diabetes (r = 0.41, p < 0.01) and controls (r = 0.45, p < 0.05). There was no association between SAF and diabetes control expressed by glycated haemoglobin. A significant relationship was observed between SAF and sRAGE in diabetes (r = 0.56, p < 0.001), but not in controls. A significant inverse association was found between SAF and MVR on the forearm in diabetes (PORH: r = -0.42, p < 0.01; TH: r = -0.46, p < 0.005). Both advanced glycation expressed by higher SAF or sRAGE and impaired MVR are involved in the pathogenesis of vascular complications in diabetes, and we confirm a strong interplay of these processes in this scenario.
Keywords: hyperemie; Humans; Soluble RAGE; Skin autofluorescence; Hyperemia; kůže; Glycation End Products, Advanced; Diabetic Angiopathies; lidé; diabetické angiopatie; Microvascular reactivity; Diabetes Mellitus; Glycated Hemoglobin A; AGEs; produkty pokročilé glykace; diabetes mellitus; Diabetes mellitus; glykovaný hemoglobin; Skin; Glycated Hemoglobin